Methods in human geography: A guide for students doing a research project - Flowerdew, Robin; Martin, David (London Routledge, 2013)
First published in 2004. This text is an essential guide to current research approaches in human geography, covering all aspects of undertaking a geography research project, from the selection of an appropriate topic through to the organisation and writing of the final report. Covering a wide range of contemporary research methods, the authors provide practical advice on how to actually undertake a project.